In vitro growth inhibition, caspase-dependent apoptosis, and S and G2/M phase arrest in breast cancer cells induced by fluorine-incorporated gold I compound, Ph3PAu[SC(OMe)=NC6H4F-3] - Richard Ming, Chuan Yu; Selvarajah, Gayathri Thevi; Geok, Chin Tan; Yoke, Kqueen Cheah (Hindawi, 2022)
Gold-based anticancer compounds have been attracting increasing research interest due to their ability to kill cancer cells resistant to platinum-based compounds. Gold I- and gold III-based complexes have shown satisfactory anticancer activities. In this study, two new fluorine-incorporated gold (I) compounds such as Ph3PAu[SC(OMe)=NC6H4F-3] and DPPFeAu2[(SC(OMe)=NC6H4F-3)]2 were evaluated for their in vitro activities against human breast cancer cell lines, primary breast cancer cells, and breast cancer stem cells (parental breast cancer stem cells, BCSC-P, and breast cancer stem cells, BCSC). Assays for growth inhibition and cytotoxicity, including real-time cell analysis, were carried out to screen effective antibreast cancer compounds. In addition, further in vitro assays such as apoptosis, caspase 3/7 activity, and cell cycle analysis were performed to observe the action and mechanism of killing breast cancer cells by the selected gold I compound, Ph3PAu[SC(OMe)=NC6H4F-3]. The gold (I) compound, Ph3PAu[SC(OMe)=NC6H4F-3], showed low toxicity to H9c2 normal cells and significant growth inhibition in MDA-MB-231 and MCF-7 cells, primary breast cancer cells, and breast cancer stem cells (BCSC-P and BCSC). The IC50 doses of the gold (I) compound Ph3PAu[SC(OMe)=NC6H4F-3] against the breast cancer cell lines MDA-MB-231 and MCF-7 were approximately 6-fold lower than that of cisplatin (cis-diamineplatinum (II) dichloride, CDDP). Moreover, the compound Ph3PAu[SC(OMe)=NC6H4F-3] induced caspase 3/7-dependent apoptosis and cell cycle arrest at S and G2/M phases. Ph3PAu[SC(OMe)=NC6H4F-3], a gold (I) compound incorporated with fluorine, is a potential candidate for the treatment of breast cancer.